2021
DOI: 10.3389/fendo.2021.691658
|View full text |Cite
|
Sign up to set email alerts
|

The Adipose Tissue at the Crosstalk Between EDCs and Cancer Development

Abstract: Obesity is a major public health concern at the origin of many pathologies, including cancers. Among them, the incidence of gastro-intestinal tract cancers is significantly increased, as well as the one of hormone-dependent cancers. The metabolic changes caused by overweight mainly with the development of adipose tissue (AT), insulin resistance and chronic inflammation induce hormonal and/or growth factor imbalances, which impact cell proliferation and differentiation. AT is now considered as the main internal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…A recurrent exposure to low doses of EDCs may interfere with the endocrine metabolism. EDCs have been implicated in the development of cancers, mainly in hormone-dependent cancers such as prostate, testis, breast, endometrium or thyroid cancer [ 45 ]. It has been shown in a fish model that EDC-responsive genes are differentially methylated after exposure to EDCs.…”
Section: Endocrine-disrupting Chemicals (Edcs) Transgenerational Impactmentioning
confidence: 99%
“…A recurrent exposure to low doses of EDCs may interfere with the endocrine metabolism. EDCs have been implicated in the development of cancers, mainly in hormone-dependent cancers such as prostate, testis, breast, endometrium or thyroid cancer [ 45 ]. It has been shown in a fish model that EDC-responsive genes are differentially methylated after exposure to EDCs.…”
Section: Endocrine-disrupting Chemicals (Edcs) Transgenerational Impactmentioning
confidence: 99%
“…It has been suggested that unlike hyperplasia (an increase in the number of adipocytes), hypertrophy is a sign of dysfunctional development of the adipocyte cells. Moreover, expanded adipocytes can lead to cellular hypoxia and chronic sub-inflammation along with an increased influx of immune cells and local increase of reactive oxygen species ( Bokobza et al, 2021 ). Therefore, markers of inflammation, and possibly, the mechanisms by which inflammation in the mammary stroma affect the long-term health of the epithelium should be evaluated in future research studies.…”
Section: Discussionmentioning
confidence: 99%
“…They are structurally highly related, as their protein sequence shares 67% identity, and include7 transmembrane domains, an extracellular carboxy-terminus and an intracellular amino-terminus, a structure that is opposite to that of all other G-coupled protein receptors. AdipoR1 and AdipoR2 are also highly conserved, since they share 95 and 97% identity between mice proteins, respectively (8)(9)(10).…”
Section: Adiponectin: Physiology and Oncogenesis-related Functionsmentioning
confidence: 99%